Study on deactivation of the CuO‐NiO/γ‐Al2O3 catalyst in the synthesis of N‐alkylmorpholines. Issue 2 (9th October 2013) - Luo, Chenxi; Qian, Chao; Luo, Hu; Feng, Lie; Chen, Yunbin; Chen, Xinzhi
ABSTRACT The performance of the CuO‐NiO/γ‐Al2O3 catalyst used in the synthesis of N‐alkylmorpholines from diethylene glycol, alcohol, and ammonia was studied. The catalyst was prepared with Ni and Cu as the active components, and the optimum contents were 4.2–4.4% and 16.8–18.9%, respectively. The catalytic activity decreased rapidly as the catalyst deactivated gradually under the high temperature and liquid hourly space velocity reaction condition. The fresh and deactivated catalysts were characterized by inductively coupled plasma atomic emission spectrometry, scanning electron microscope, X‐ray diffraction, thermo gravimetric analyzer, element analysis instrument and N2 adsorption–desorption. It was found that the catalyst was covered with carbon deposition, which stunted the active center of catalyst surface and blocked the channels of the support. In addition, the sintering of the copper crystallites resulted in reunion of active metal and reduction of the active sites. At last, the catalysts were regenerated by calcination with high temperature, and the yield of the regeneration catalytic reaction was restored to 88.9% of its original levels. Copyright © 2013 Curtin University of Technology and John Wiley & Sons, Ltd.